To What Extent is GenAI Relevant to Empowering Students' Critical Thinking and Creative Thinking Skills? - Nofamataro Zebua (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Advances in technology, particularly Generative AI (GenAI), have opened up great opportunities in improving critical and creative thinking skills in education. It offers the potential for personalizing learning, strengthening collaboration, and creating innovative environments that support the development of essential 21st century skills. This article discusses the relevance and implementation of GenAI in learning, examining the benefits it brings, such as increased student analysis and innovation, as well as the challenges faced, including technology dependency, accessibility gaps, and teacher training needs. With thoughtful implementation strategies, GenAI can be a catalyst for empowering students in an inclusive manner, although it requires regulations and policies that support its sustainability and equitable distribution of benefits. The results of this discussion confirm that the integration of GenAI in education requires a holistic approach to ensure its significant impact on student learning and skill development.